A General and Efficient Synthesis of 2‐Pyridones, 2‐Quinolinones, and 1‐Isoquinolinones from Azine N‐Oxides. Issue 12 (24th October 2016) - Wang, Dong; Zhao, Junjie; Wang, Yuxi; Hu, Jianyong; Li, Linna; Miao, Longfei; Feng, Hairong; Désaubry, Laurent; Yu, Peng
Abstract: 2‐Pyridones, 2‐quinolinones, and 1‐isoquinolinones are critical building blocks in medicinal chemistry. These N‐heterocycles, however, remain a challenge to synthesize by current methods. A mild, general, and efficient approach for the synthesis of these hydroxyl N‐heteroarenes was developed by employing bromotripyrrolidinophosphonium hexafluorophosphate (PyBroP) as an activating agent and sodium acetate/water as the base/nucleophile combination. The reaction mechanism, especially the dual function of sodium acetate as the base and nucleophile, has been proposed on the basis of results from isotopic labeling experiments. Abstract : N‐O Metal ! We report the synthesis of hydroxyazines under mild conditions from their N ‐oxide precursors by using bromotripyrrolidinophosphonium hexafluorophosphate (PyBroP) as an activating agent and sodium acetate/water as the base/nucleophile combination. The approach is applicable to N‐heteroarenes, such as quinolines, isoquinolines, and pyridines. A 70 % average yield among 25 successful reactions with up to a 95 % product yield was achieved. PyBroP=bromotripyrrolidinophosphonium hexafluorophosphate, DCE=1, 2‐dichloroethane.